Digital Ulcers in Ssc Treated with Oral Treprostinil: A Randomized, Double-Blind, Placebo-Controlled Study with Open-Label Follow-up. Issue 1 (January 2017) - Seibold, James R.; Wigley, Fredrick M.; Schiopu, Elena; Denton, Christopher P.; Silver, Richard M.; Steen, Virginia D.; Domsic, Robyn; Medsger, Thomas A.; Mayes, Maureen D.; Chatterjee, Soumya; Chung, Lorinda; Csuka, Mary Ellen; et al.
Background: Prostacyclins are routinely used to treat vascular features of systemic sclerosis (SSc, scleroderma) but require parenteral infusion or inhalation. This study evaluated the safety and efficacy of oral treprostinil in digital ulcers secondary to SSc. Methods: This was a randomized (1:1) placebo-controlled, multicenter study in adults with SSc and at least one active digital ulcer at entry. Oral treprostinil was administered twice daily and titrated to maximum tolerated dose with clinical assessments at Weeks 5, 10, 15 and 20. The primary endpoint was change in net digital ulcer burden. Secondary outcomes included ulcer healing and prevention, measures of hand function, quality of life, Raynaud phenomenon and global assessments. Simplified data were gathered during open-label follow up. Results: Enrolled were 147 patients (109F/38M), mean age 48.8 years with SSc of mean duration 10.5 years. At week 20, mean net ulcer burden was reduced −0.43 ulcers on treprostinil (1.80 vs. 1.37) and −0.10 ulcers on placebo (1.61 vs. 1.51; p = 0.20). There were no effects on ulcer healing or prevention, and small, inconsistent effects on Raynaud phenomenon, global assessment, hand function and quality-of-life measures. In open-label follow-up, there was a continued, small reduction in net ulcer burden (-0.52 month 3, n = 104; −0.64 month 12, n = 36). Common adverse effects were headache, nausea, diarrhea, jaw pain, flushing and other gastrointestinal symptoms. Conclusions: Administration of oral treprostinil twice daily over 20 weeks was associated with small and statistically insignificant reduction in net ulcer burden in comparison to placebo.